Venous thromboembolism and mortality in breast cancer: cohort study with systematic review and meta-analysis - Khan, U; Walker, A; Baig, S; Card, T; Kirwan, C; Grainge, M (BioMed Central, 2017)
Background: Breast cancer patients are at an increased risk of venous thromboembolism (VTE). However, current evidence as to whether VTE increases the risk of mortality in breast cancer patients is conflicting. We present data from a large cohort of patients from the UK and pool these with previous data from a systematic review. Methods: Using the Clinical Practice Research Datalink (CPRD) dataset, we identified a cohort of 13,202 breast cancer patients, of whom 611 were diagnosed with VTE between 1997 and 2006 and 12,591 did not develop VTE. Hazard ratios (HR) were used to compare mortality between the two groups. These were then pooled with existing data on this topic identified via a search of the MEDLINE and EMBASE databases (until January 2015) using a random-effects meta-analysis. Results: Within the CPRD, VTE was associated with increased mortality when treated as a time-varying covariate (HR = 2.42; 95% CI, 2.13-2.75), however, when patients were permanently classed as having VTE based on presence of a VTE event within 6 months of cancer diagnosis, no increased risk was observed (HR = 1.22; 0.93-1.60). The pooled HR from seven studies using the second approach was 1.69 (1.12-2.55), with no effect seen when restricted to studies which adjusted for key covariates. Conclusion: A large HR for VTE in the time-varying covariate analysis reflects the known short-term mortality following a VTE. When breast cancer patients are fortunate to survive the initial VTE, the influence on longer-term mortality is less certain.